A pollution sensitive remanufacturing model with waste items: Triangular dense fuzzy lock set approach. (20th June 2018) - Karmakar, Snigdha; De, Sujit Kumar; Goswami, A.
Abstract: This study considers an economic production quantity model for both production and recycling under pollution reduction. However, for developing the model, at first we develop a functional relationship among the production rate, remanufacture rate and the pollution rate with the help of prey-predator relationship, then we have investigated a production-remanufacturing process in reverse logistics associated with the returned items. Examining real case study of a Sponge-iron (SI) industry, it is observed that how recycling reduces the environmental pollution and increase the livelihood status of the people associated with collecting scrap and used items for recycling in the production process itself. To validate the model statistically, we have utilized the normal distribution and computed p -values. Due to financial constraints of industrial management, we have studied the flexibilities of different cost vectors by means of the Triangular dense fuzzy lock set (TDFLS) rule along with its locking and unlocking property for final decision-making. Moreover, our findings suggest that the decision maker (DM) might have to focus on remanufacturing and recycling for pollution reduction and creation of jobs. Finally, we have shown that the DM might have to adapt the TDFLS rule to reduce the pollution and financial loss for socio-economic sustainable development. Graphical abstract: Image 1 Highlights: A production- recycling inventory model with pollution is considered. Relation among pollution rate, production rate and remanufacture rate has been derived. Environmental risk factor due to over-production has been considered. Dense fuzzy lock set theory concept is incorporated in the model.